2010
DOI: 10.2967/jnumed.110.075390
|View full text |Cite
|
Sign up to set email alerts
|

Objective Detection of Epileptic Foci by18F-FDG PET in Children Undergoing Epilepsy Surgery

Abstract: PET has been used for the presurgical localization of epileptic foci for more than 20 y; still, its clinical role in children with intractable epilepsy remains unclear, largely because of variable analytic approaches and different outcome measures. The purpose of the present study was to evaluate and optimize the performance (lateralization and lobar localization value of epileptic foci) of objective voxel-based analysis of 18F-FDG PET scans in a pediatric epilepsy population. Methods Twenty children with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 36 publications
7
118
0
2
Order By: Relevance
“…Kumar et al 23 compared the results between V and SPM. The reported sensitivity from that study was 62% for V and 71% for SPM using a threshold of p < 0.001 (35% with a stricter threshold of p < 0.05).…”
Section: With Respect To Surgical Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al 23 compared the results between V and SPM. The reported sensitivity from that study was 62% for V and 71% for SPM using a threshold of p < 0.001 (35% with a stricter threshold of p < 0.05).…”
Section: With Respect To Surgical Decision Makingmentioning
confidence: 99%
“…23,[38][39][40] In one study, 23 the results for two methods of PET interpretation-visual analysis (V) and statistical parametric mapping (SPM)-were reported. SPM using a threshold of p < 0.001 provided a sensitivity of 86% when measured against intracranial EEG.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…Static 18 F-FDG PET image volumes were analyzed using the SPM8 software package developed at the Wellcome Department of Cognitive Neurology, Institute of Neurology (21). 18 F-FDG PET image volumes were spatially normalized into standard stereotactic space using an in-house pediatric PET template.…”
Section: Pet Image Analysismentioning
confidence: 99%
“…In one study reported by Ibrahim et al, for example, the time from seizure onset to tumour diagnosis among ten children presenting with seizures ranged from two weeks to two years, averaging six months [37]. A wide range of opinions and practices exist regarding how aggressive to pursue diagnostic imaging in children presenting with seizures [36,41,51,79,80,100,[127][128][129][130][131][132][133]. For example, in one series of eighteen patients between the ages of 1 month and 13 years who presented with seizures and were discovered to have DNETs between January 1992 and December 2004, the preoperative evaluation included magnetic resonance (MR) imaging and interictal scalp electro-encephalography (EEG) in all patients, but functional MR imaging also was performed in eight patients, video monitoring with scalp EEG during seizures in 12 patients, interictal single-photon emission computerized tomography (SPECT) scanning in one patient, and ictal SPECT scanning in two patients [132].…”
Section: How Seizures Presentmentioning
confidence: 99%